Underground Measurement of Magnetic Field Pulses During the Early Stage of Rocket‐Triggered Lightning. Issue 6 (21st March 2019) - Li, Xiao; Lu, Gaopeng; Fan, Yanfeng; Jiang, Rubin; Zhang, Hongbo; Li, Dongshuai; Liu, Mingyuan; Wang, Yongping; Ren, Huan
Abstract: We examined the underground magnetic field near the lightning channel with low‐frequency magnetic sensor based on SHAndong Triggering Lightning Experiment (SHATLE). Two sensors were deployed, one at 1‐m height above ground and another one at 2‐m depth underground at a distance of 78 m from the lightning channel, and the magnetic pulses during the initial stage of triggered lightning were recorded. The experimental results show that the microsecond‐scale magnetic pulses radiated by the upward lightning leader can be detected in the subsurface space and the magnetic signal is modified by the soil medium. Specifically, the amplitude at the depth of 2 m is attenuated typically more than 55%, and the attenuation decreases as the timescale of the magnetic pulse increases; meanwhile, the peak time of the underground magnetic pulse is delayed by about 0.6 μs, and the half‐peak width of the magnetic pulse is increased by 0.2–0.8 μs (namely, by 20% to 32%). The results of Fourier analysis indicate that the component with relatively high frequency is subject to more attenuation than is the component with relatively low frequency. In addition, the simulation of magnetic field with the channel‐base current by using the transmission line model is consistent with the measurement, indicating that the modification on the waveform characteristics of the lightning pulse measured underground could provide valuable information for retrieving the electromagnetic parameters of soil. Plain Language Summary: The broadband electromagnetic radiation of lightning discharges can penetrate the soil and affect the underground electronic facilities, and meanwhile, the detection of lightning signals below the ground surface can be used as a tool to explore the underground space. To investigate the influence of soil medium on the lightning radiation, the low‐frequency magnetic sensors are deployed at 1‐m height above the ground and 2‐m depth underground to measure the magnetic field pulse at a distance of 78 m from the lightning channel artificially created in the rocket‐triggered lightning experiment. After the magnetic field pulse propagates through the soil, the amplitude of the pulse waveform attenuates, the half‐peak width increases, and the peak time delays. The variation in the waveform characteristics is quantified and analyzed. We discuss the reason for the variation of characteristics, which is related to the timescale of the pulse. In addition, relevant simulation was developed based on the transmission line model, and the result is consistent with the measured data. It is possible to invert formation electromagnetic parameters according to the variation of the waveform characteristics. Key Points: The waveform of magnetic pulses radiated by lightning discharges as measured at 2‐m depth is modified due to the propagation through soil The modification of magnetic pulses caused by the propagation through soil depends on the timescale of the magnetic pulse Preliminary simulation of near‐range magnetic field is carried out based on channel‐base current with the transmission line model